Kajian Status Kesuburan Tanah untuk Menentukan Pemupukan Spesifik Lokasi Tanaman Padi - I NYOMAN PUJA; I WAYAN DANA ATMAJA (Fakultas Pertanian Universitas Udayana, 2018)
Study of Soil Fertility Status to Determine Specific Fertilizer Locations of Rice Plants. Soil fertility status is one of the tools to determine balanced fertilization. The use of inorganic fertilizers continuously at high doses will accelerate the depletion of other elements which cause imbalance of nutrients in the soil. This research was carried out in Abang-Karangasem District. The purpose of this study was to compile location-specific fertilizer recommendations based on their soil fertility status. This research was conducted by survey and laboratory analysis method with activity step: preparation (making of land unit), field survey, soil sample analysis, evaluation of soil fertility status and determination of location-specific fertilizer recommendations. The results showed that soil fertility status in Abang District is low and medium. Recommended fertilization without straw return for areas with low fertility status are 250 kg Urea/ha, 100 kg SP36/ha and 50 kg KCl/ha. Whereas if with straw returned (5 t/ha) are 230 kg Urea/ha, 100 kg SP36/ha and 50 kg KCl/ha. Recommended fertilization without straw return for areas with medium fertility status are 250 kg Urea/ha, 75 kg SP36/ha and 50 kg KCl/ha. Whereas if with straw returned (5 t/ha) are 230 kg Urea/ha, 50 kg SP36/ha and 0 kg KCl/ha.